Tinjauan Pelaksanaan Pengisian Formulir General Consent Rawat Inap RSUP Dr. Sitanala Kota Tangerang Tahun 2021 - Setiawan Irwansyah; Noor Yulia; Daniel Happy Putra; Nanda Aula Rumana (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
General consent is an agreement signed by the patient’s family at the inpatient registration. The purpose of this research is to describe the implementation of filling out the general consent form at Dr. RSUP. Sitanala Tangerang City. Using descriptive method with quantitative analysis of observation and interviews. Cross sectional design, non-random sampling of the patient’s family at the inpatient registration place. Result the officer explained how to fill out the general consent form only to 86 patient's family (57.3%), explained the purpose of filling only 24 patient's family (16%), explained the procedure for filling out the to 90 patient's family (60%), explained the contents of the form to 68 patient's family (44%), the factors that influenced the incomplete filling of the general consent from were the officers did not explain in detail how to fill out the complete form, factors from the patient's family are those who rush to fill in, don’t listen to detailed explanations, did not understand ethe explanation given by the officer but was lasy to ask, afraid to ask research suggestions, audit filling out the general consent form according to standard operating prosedures.